2018
DOI: 10.3390/toxins10120533
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Contamination with Mycotoxins in the Context of the Geographic and Agroclimatic Conditions in Romania

Abstract: This study aimed to assess post-harvest contamination with mycotoxins in the context of the geographic and agroclimatic conditions in Romania in 2012–2015, a period that was characterized by extreme meteorological events and the effects of climate change. The samples were randomly sampled from five agricultural regions of Romania and analyzed for mycotoxins by enzyme-linked immunosorbent assay. An SPSS analysis was done to explore correlations between mycotoxins (deoxynivalenol—DON, aflatoxins—AF, ochratoxin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 42 publications
(65 reference statements)
6
31
0
Order By: Relevance
“…The same conclusion was also reached by Alexa et al [32] after analyzing 52 wheat samples collected from Western Romania during two consecutive harvest years. The newest data published about mycotoxins in Romanian wheat concluded that post-harvest contamination with DON and ZEN has a local character, with the Southern part of Romania being the area of interest due to its semi-arid temperate continental climatic conditions [38].…”
Section: Resultsmentioning
confidence: 99%
“…The same conclusion was also reached by Alexa et al [32] after analyzing 52 wheat samples collected from Western Romania during two consecutive harvest years. The newest data published about mycotoxins in Romanian wheat concluded that post-harvest contamination with DON and ZEN has a local character, with the Southern part of Romania being the area of interest due to its semi-arid temperate continental climatic conditions [38].…”
Section: Resultsmentioning
confidence: 99%
“…Several surveys on the worldwide contamination of Fusarium toxins in cereals and cereal products during the last decade indicate the importance of the problem that food safety is facing globally [ 3 , 4 , 5 , 19 , 28 , 32 ]. Several papers presented data on the Fusarium mycotoxins occurrence from European countries [ 9 , 18 , 20 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. These data have shown high contamination rates, ranging from 20% to 100% for DON, 11% to 95% for FBs, from 1% to 100% for T-2, from 4% to 60% for HT-2 and from 71% to 100% for ZEA.…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of the stored maize could also influence the activities of insect pests, which may also be relationship with mycotoxin levels [17,30]. For in-field contaminated cereals, a very significant correlation of DON with regions and meteorological factors (air temperature, precipitation, relative humidity) has been reported [31]. In corn, ZEN and DON may cooccur in preharvest and postharvest and could also increase during storage [32].…”
Section: Quality Changes Of Maize Germ Oils During Storagementioning
confidence: 99%